Teaching to multiple intelligences - Thompson, Jim ([S.l.] : Jim Thompson [production company] ; [S.l.] : Quality Educational Media [distributor], 1997)
Discussed on the multiple intelligences
Editor, Wayne Threm
Keywords: Multiple intelligences; Teaching; Learning